A qualitative metasynthesis of teacher educator self-studies on social justice: Articulating a social justice pedagogy. (March 2023) - Jacobs, Jennifer; Perez, Jennifer I.
Abstract: Teacher preparation programs are vital to facilitating the development of teacher candidates who have the knowledge, skills, and dispositions that align with a social justice approach to teaching. However, enacting teacher preparation for social justice will necessitate teacher educators with sophisticated expertise. To gain insight into this enactment, we engaged in a qualitative metasynthesis of teacher educator self-studies about teacher preparation for social justice. Teacher educator self-studies serve as a context for teacher educators to study and problematize their practice while also contributing to the larger teacher education literature base. The qualitative metasynthesis examined 65 teacher educator self-studies from 1992 to 2021 across journal articles, books, and conference proceedings. The analysis and synthesis of the teacher educator self-studies resulted in naming three components necessary for facilitating teacher candidate social justice learning within the context of teacher preparation: 1) Centralizing the Lens of Identity, 2) Classroom Environment Conducive to Social Justice Learning, and 3) Pedagogical Practices to Promote Critical Consciousness and Praxis. Within each of these components are high-leverage practices and routines of practice that can be utilized to enact that component. Taken together, the findings result in a framework for a pedagogy of teacher education for social justice rather than focusing solely on what teacher candidates need to know and be able to do. The findings have implications for teacher educator professional learning, program design, and future approaches to research. Highlights: Qualitative metasynthesis of social justice teacher educator selfstudies Metasynthesis produced a framework for social justice teacher preparation pedagogy Focus on teacher educator identity needed Creation of a classroom environment conducive to social justice learning Promoting critical consciousness and praxis through pedagogy